THE ISOLATION OF AN O SPECIFIC SUBSTANCE FROM GASTRIC JUICE OF SECRETORS AND CARBOHYDRATE-LIKE SUBSTANCES FROM GASTRIC JUICE OF NON-SECRETORS - Witebsky, Ernest (The Rockefeller University Press, 1941)
1. The isolation of a group specific O substance from the gastric juice of human beings belonging to group O is described. Absorbed normal beef serum constitutes the anti-O reagent. 2. The O specific substance inhibits the agglutination of human red blood cells belonging to group O. The agglutination of A cells by the isoagglutinin anti-A, or B cells by the isoagglutinin anti-B, is not influenced by the O substance. 3. The A and B specific substances isolated from human gastric juices inhibit the agglutination of O cells by absorbed normal beef serum, frequently to about the same extent as does the O substance itself. 4. The carbohydrate fraction isolated from the gastric juice of non-secretors belonging to group B does not inhibit the agglutination of human red blood cells of group B by the isoagglutinin anti-B nor the agglutination of O cells by the anti-O reagent. The significance of these findings for the conception of the nature of the blood groups and their inheritance is discussed.